Hooked on heroin: drugs and drifters in a globalized world - Lalander, Philip (Berg, 2003)
Under the city's shell -- Before heroin -- The secret cave -- The threats that divide and unite -- Doing drugs with honour and style -- Who is directing? -- The subculture's gender code -- The whole world is yours.